Effects of ARID1A loss on transcriptional regulation in hepatocellular carcinoma cell line PLC/PRF/5 - WANG Ding-ding, LIANG Jun-bo, WANG Xiao-yue (Jichu yixue yu linchuang, 2020)
Objective To explore the transcriptional alterations regulated by ARID1A in hepatocellular carcinoma cell line PLC/PRF/5. Methods CRISPR/Cas9 technology was utilized to generate ARID1A knockout cells. RNA-seq was then performed in both ARID1A intact and ARID1A null PLC/PRF/5 cells to generate gene expression profiles. Differentially expressed genes were identified using DESeq2. Functional enrichment analysis of differentially expressed genes was performed using metascape database. Results Successful generation of the ARID1A knockout PLC/PRF/5 cells was confirmed by Western blot and Sanger sequencing. A total of 978 differentially expressed genes were identified by RNA-seq, among which the expression of 480 genes was up-regulated and that of 498 genes was down-regulated. These differentially expressed genes were mainly enriched in several biological processes including cell adhesion, regulation of hormone levels, hormone metabolism and regulation of MAP kinase activity. Conclusions The results indicate that ARID1A loss induces alterations in transcription in PLC/PRF/5, which may provide novo clues for elucidating the underlying mechanism of ARID1A in tumorigenesis.